Penajaman Citra Satelit Landsat 8 Menggunakan Transformasi Brovey - Pradipta, I Made Dhanan; Widyantara, I Made Oka; Hartati, Rukmi Sari (Majalah Ilmiah Teknologi Elektro; Vol 18 No 3 (2019): (September - Desember) Majalah Ilmiah Teknologi Elektro, 2019)
Abstract—Image sharpening is an image optimization technique by combining two satellite images by taking advantage of each images, so that the output image has good spectral and spatial quality. Image sharpening is an alternative to facilitate the recognition of an object, moreover for Landsat satellites has many bands that can be used as samples for the image sharpening process. One method used in image sharpening is Brovey Transformation. This method is widely used because it is very simple and easy in making the algorithm. The Bands which is used in the image sharpening process are composite bands (red, green, and blue) with panchromatic bands from the Landsat 8 satellite. The results of the image sharpening process are high spectral images obtained from composite images and spatial values obtained from panchromatic images. Analysis of the results of image sharpening using the Brovey Transform method is done by comparing the quality of the truecolor image before sharpened and the image that has been sharpened by calculating the maximum and minimum values of the red, green and blue bands, analyzing the mean values and also the standard deviation values of each image. Key Words— Brovey Transformation, Composite, Image Sharpening, Landsat 8